(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This paper investigated the impact of adequate funding on universities development in North-central Nigeria. The survey research design was adopted for this study. The population of the study was made up of 480 academic staff from four federal universities located in the North-Central Nigeria. Stratified random sampling technique was used to select the sample size of 480. Questionnaire was adopted as instrument for data collection. The questionnaire was validated experts in educational administration and planning and it reliability test yielded 0.72 index which were obtained by test-retest method. A decision point of 2.50 was set and used to accept or reject any item in the items questions. Mean and standard deviation were used to analyses data. Hypotheses were tested by Pearson Moment Product Correlation Coefficient. The findings showed that there is significant relationship between adequate funding and implementation of teaching, research and community service programme of universities in North-central Nigeria. Based on these findings, the paper hereby recommended that government should increase the funding of the universities in the North-Central, Nigeria. Universities administrators should think outside the box and improve the internally generated revenue of the various universities in the region. International organizations should support universities with financial aids to enable them execute their programmes.